Effectiveness of "Marital Skills training for mastectomy women" in improving marital satisfaction of husbands - Bahman Bahmani; Mahdieh Babarabie; Ali Ghanbari Motlagh; Ahmad Izadi; Nezamaddin Ghasemi (Gonabad University of Medical Sciences, 2017)
One of the health issues related to patients suffering from cancer is paying attention to mental health of the patients and their families. This research was carried out to determine the effect of teaching marital life skills for mastectomy women in the increase of marital satisfaction of this group of patients as well as its direct effect on their spouses' satisfaction. This was a quasi-experimental research designed as pretest/posttest with random assignment and control group. 22 women suffering from breast cancer, undergoing mastectomy, treated by radiotherapy and having marital satisfaction lower than the moderate level based on the short form (40-question) of the ENRICH (evaluation and nurturing relationship issues, communication and happiness) questionnaire were selected via purposive sampling and divided into experimental and control groups using random assignment. The pretest was carried out on experimental and control groups and the husbands. The intervention was performed during 12 didactic sessions, two a week, for women of the experimental group in the absence of their husbands. Results indicated that the mean score of marital satisfaction in mastectomy women and their husbands in the experimental group was higher than that of the control group, and the difference was statistically significant. In conclusion, the combined intervention method used in this research was effective in increasing marital satisfaction of mastectomy women, and had also a positive effect on their husbands' marital satisfaction.